Ethnicity, age, and education influence perceptions of vegetable healthiness and macronutrient content. Issue 4 (December 2022) - Aram, McKenna; Smallman, Rachel; Fields, Sherecce A.; Larez, Arianna; Glantz, Namino; Kerr, David
Objective: To assess perceptions of nutritional content and health value of popular vegetables.Design: Cross-sectional online survey.Participants: A total of 760 adults participated in the study.Main Outcome Measures: Likert scale ratings of healthy, calories, carbohydrates, protein, and fiber, for (i) avocado, (ii) romaine lettuce, (iii) white potato, (iv) white onion, and (v) red tomato.Analysis: ANOVAs for continuous variables and Chi-square for categorical variables. Outcomes for nutritional content were compared using separate one-way ANOVAs with ethnicity (Hispanic/Latino vs. non-Hispanic); education (college degree/no college degree); age (18–34, 35–50, 51–70, 70 + ); and diabetes status (with or without diabetes) as the grouping variables.Results: Significant ethnicity effects were found for avocado, lettuce, potato, onion, and tomato. Education level effects were found for avocado, lettuce, potato, and tomato. Age level effects were found for avocado, lettuce, potato, and tomato.Conclusions and Implications: Participant perceptions of the macronutrient content of common vegetables and fruits largely coincided with the US Department of Agriculture values. However, stratifying by ethnicity, age, and education revealed significant differences in both macronutrient perceptions and perceived healthiness. There were no consistent, significant results for interactions of ethnicity by education, nor ethnicity by age. These results suggest that dietary interventions may need to be adjusted based on participant sociodemographic characteristics linked to the perceptions of nutritional value and healthiness.